Estimation of chlorophyll content in intertidal mangrove leaves with different thicknesses using hyperspectral data. (November 2019) - Zhao, Yunxia; Yan, Chunhua; Lu, Shan; Wang, Pei; Qiu, Guo Yu; Li, Ruili
Highlights: Chl content is hyperspectral remotely estimated in four intertidal mangrove species. IMDATT performs best and shows low sensitivity to the variations of leaf surfaces. IMDATT is most effective for intertidal mangrove species with thin leaves. The performances of IMDATT differs with species, as well as leaf thickness. Abstract: Mangrove forests worldwide are mostly degrading and the degradation can be monitored by the leaf chlorophyll (Chl) content, which can be estimated from a quick non-destructive remote measurement. Although there are extensive studies on spectrometric remote sensing methods, few studies on intertidal mangroves are available, and the non-destructive Chl content monitoring method for mangrove with unique leaf characteristics has not been proposed. To develop a valid, non-destructive method for Chl estimation, this study examined nine commonly used vegetation indexes (VIs) for both adaxial and abaxial leaf surfaces of four mangrove species with different leaf thicknesses. Results showed that the modified Datt index (MDATT) was the most effective for estimating the Chl content for both leaf surfaces of various species. An improved MDATT index (IMDATT), in the form of ( R527  −  R746 )/( R527  −  R747 ), performed best with r  = −0.88 and RMSE  = 8.70 µg/cm 2, among all the optimal VIs tested, and proved to be applicable to monitor Chl content with low sensitivity to the variations of leaf surfaces. It proved to be applicable to monitor Chl content in the validation data sets of all species ( r  = 0.87 and RMSE  = 8.20 µg/cm 2 ) and it could be more effective for specific species, with larger r and smaller RMSE . In addition, the different performances of IMDATT could be attributed to the species, as well as the leaf thickness. In conclusion, IMDATT could be broadly applicable to intertidal mangrove plants, especially for species with thin leaves. The research provides a robust tool for monitoring mangrove Chl content.